Finegoldia magna infection after lumbar spine surgery determined based on targeted next-generation sequencing - Wanli Feng; Boyang Sun; Rong’an Shang; Zhen Li; Liqiang Lei; Jian Kang (BMC Musculoskeletal Disorders)
Abstract Introduction Facultative anaerobic bacteria are the predominant pathogens in postoperative lumbar spine infections, while gram-positive anaerobic cocci, such as Finegoldia magna (F. magna), act as opportunistic pathogens and are among the most virulent. We report an elderly woman who suffered Finegoldia infection after lumbar spine surgery. To the best of our knowledge, this is the first well-documented case in the literature. Case description A 67-year-old female underwent a multi-segmental posterior lumbar interbody fusion surgery for lumbar spinal stenosis. On postoperative day 11, central surgical incision dehiscence was noted, accompanied by wound discharge and lumbar-hip pain. Wound secretions were cultured four times and all tested negative for bacteria. The causative agent was identified as F. magna via targeted next-generation sequencing (tNGS) combined with traditional microbial smear microscopy. After 4 days of piperacillin-tazobactam, the patient developed persistent high fever (39.5℃), prompting a cautious switch to combination therapy with vancomycin and metronidazole, which resolved the infection effectively. Conclusion F. magna is an uncommon cause of post-lumbar spine surgery infection, warranting a high index of suspicion for this gram-positive anaerobic coccus. When F. magna infection is encountered, treatment with vancomycin or metronidazole may be considered when antimicrobial susceptibility testing is not available.